Reviews - de estudios ingleses, Revista alicantina (Alicante Journal of English Studies / Revista Alicantina de Estudios Ingleses, 2003)
Contiene: Jussawalla, Feroza (2003): Chiffon Saris. Toronto: TSAR Publications, 92 pages / Reviewed by Silvia Caporale Bizzini; Fernández Álvarez; M. Pilar and Antón Teodoro Manrique (2002): Antología de la literatura nórdica antigua. Salamanca: Ediciones Universidad / Reviewed by José R. Belda; Schwarlz, Anja (2001). The (im)possibilities of machine translation. Peter Lang. Frankfurt am Main. 323 pages / Reviewed by Silvia Borrás Giner; Terttu Nevalainen and Helena Raumolin-Brunberg (2003): Historical Sociolinguistics: Language Change in Tudor and Stuart England. Great Britain: Pearson Education, 260pages / Reviewed by Sara Ponce Serrano.Contiene: Jussawalla, Feroza (2003): Chiffon Saris. Toronto: TSAR Publications, 92 pages / Reviewed by Silvia Caporale Bizzini; Fernández Álvarez; M. Pilar and Antón Teodoro Manrique (2002): Antología de la literatura nórdica antigua. Salamanca: Ediciones Universidad / Reviewed by José R. Belda; Schwarlz, Anja (2001). The (im)possibilities of machine translation. Peter Lang. Frankfurt am Main. 323 pages / Reviewed by Silvia Borrás Giner; Terttu Nevalainen and Helena Raumolin-Brunberg (2003): Historical Sociolinguistics: Language Change in Tudor and Stuart England. Great Britain: Pearson Education, 260pages / Reviewed by Sara Ponce Serrano.